(untitled) (Dhaka University Journal of Biological Sciences, 2020)
Personal care products are part of our everyday life and it is a large industry. It is very important for marketers to know what consumers give importance to when they buy these products. It will help them to produce, design and promote products focusing consumer’s need and attract more consumers. This work is a cross-sectional survey which focuses on choice opinions of consumers of Dhaka city. Primary data were collected from 300 people using a 15 item questionnaire with 5 point Likert scale. Analysis shows mean rank of 6 factors (Specialized product, M = 3.953, rank 1 to word of mouth, M = 2.200, rank 6), significant difference in one tailed t test between male and female in factor 1- specialized products (tc = 4.702 > tt = 1.65) and different mean rank among people from 5 different professions (for student, service holder and businessman, rank 1 - specialized products; for unemployed and housewife, rank 1 - characteristics of product). Present study also explored opinions of people having different education levels but did not find any significant difference. Dhaka Univ. J. Biol. Sci. 29(1): 53-59, 2020 (January)